The Effect Of The Healthy Clean Live Knowledge (Phbs) Toward Student Personal Cleanliness By Using A Saintific Approach At The Fourth And Fifth Grade Students In The Environment Of Sd Negeri 04 Minas - Rahmayulis Rahmayulis (Fakultas Sastra Universitas Ekasakti, 2018)
Factors affecting individual health and public health are heredity, environment, behavior and public service (Soekidjo Notoatmodjo, 2010). In addition to factors affecting health, there are factors that influence clean life behavior, among others social class and economy class, knowledge, attitude, health status and personal habits. In relation to this matter, SD Negeri 04 Minas is a Primary School which has applied about healthy clean living in school by giving the material about school environment health. But in reality SD Negeri 04 Minas are less clean and tidy in dressing and shodding, picket cleaning classrooms that should always be reminded, there is a garbage disposal is not in place, students do not wash hands after exercise and before eating, students have cavities, Students have long and unsanitary nails, and students have less clean hair (there are ticks). Based on the phenomenon exists can be concluded that on the students. Based on the background and identification of problems that have been mentioned above, then the problem in this research is